REDESAIN PASAR TRADISIONAL TOMOHON DENGAN PENDEKATAN ARSITEKTUR NEO-VERNAKULAR DI KOTA TOMOHON - Moloku, Semuel; Budhyowati, M.Y. Noorwahyu; Kawatu, Freike E. (Program Studi Arsitektur Fakultas Teknik Universitas Negeri Manado, 2024)
Traditional markets are places for buying and selling transactions for food necessities. One of the markets in Tomohon City is the traditional market (Pasar Beliman Tomohon), a market with conditions that appear to be irregular in terms of the grouping of food types and circulation that is not well mapped. As time went by, traders began to fill up on the sides of the road, disrupting transportation activities on the highway. In general, the city of Tomohon is located in a strategic place, apart from being known as an educational city and tourist destination, this city is also known as a city that has traditional markets in Indonesia in North Sulawesi. Broadly speaking, usually the market is known as the process that occurs between buyers and sellers in reaching an agreement on price. And seeing this phenomenon, especially the increasing presence of visitors from within the city and from outside the city, this has triggered the development of a market that is increasingly crowded with the activities of traders and buyers. The application of Neo-vernacular architecture in the design of this traditional market can provide a representative image of the city of Tomohon, including the Paslaten 1 sub-district, which expresses elements of the shape of the surrounding environment as well as models of craft products from the Paslaten sub-district.